Anthropogenic Carrion Subsidy and Herbicide Glyphosate Depressed Leaf-Litter Breakdown: Effects on Environmental Health in Streams - Xiang, Hongyong; Zhang, Yixin; Atkinson, David; Sekar, Raju (Frontiers in Environmental Science, 2022)
Terrestrial leaf-litter (LL) inputs impose great bottom-up effects on freshwater ecosystems by fueling detritus-based food webs, affecting macroinvertebrate and microbial communities, and influencing ecosystem functioning. However, increasing intensive anthropogenic activities including the inputs of anthropogenic subsidies and herbicide glyphosate have disturbed the breakdown of LL in streams. Here, we used chicken meat as an anthropogenic carrion subsidy and glyphosate as a stressor to investigate their individual and combined effects on LL breakdown in urban and forest streams in China. We found that: (1) carrion subsidy decreased LL breakdown rate while had no effect on macroinvertebrate communities, the declined LL breakdown rates may be attributed to the foraging shift of macroinvertebrates from LL to carrion subsidy and stronger predatory pressure of Erpobdellidae on other macroinvertebrates in forest and urban streams, respectively; (2) glyphosate depressed LL breakdown rate and showed no impact on macroinvertebrate communities, the declined LL breakdown rate may be caused by the negative effects on microbes; (3) forest streams showed significantly higher LL breakdown rates than urban streams which were induced by the high dissolved oxygen (DO) and macroinvertebrate richness in forest streams. Our results provide evidence that LL breakdown in streams is sensitive to the inputs of anthropogenic carrion subsidy and glyphosate through the impacts on macroinvertebrates and microbes, respectively. Furthermore, this study underscores the importance of land-use scenario when assessing the responses of stream ecosystem functioning and macroinvertebrate communities to multiple stressors, as the individual and combined effects of stressors may be different in streams with varying physical characteristics and surrounding land-use patterns.